Do You Feel Welcome? Gendered Experiences in International Security Studies. Issue 1 (5th December 2019) - Rublee, Maria Rost; Jackson, Emily B; Parajon, Eric; Peterson, Susan; Duncombe, Constance
Abstract: Unlike in the broader field of international relations, relatively little research on gender representation and gendered experiences exists within the subfield of security studies. This article begins to fill that gap by sharing the results of a 2019 survey of members of the International Security Studies Section (ISSS) of the International Studies Association (ISA). The survey results show striking gender differences in members' experiences, with women more likely than men to describe ISSS as "insular, " "clubby, " and an "Old Boys' Network"; more likely to report experiences of hostility and exclusion; and more likely to believe that diversity initiatives are needed. Our analysis reveals that women in the ISSS report (1) harassment, (2) negative experiences participating in various section activities, (3) more significant barriers to attending and being selected for the section's ISA program, and (4) a sense of feeling unwelcome at ISSS meetings, all at higher rates than male respondents.